Body growth and alimentary tract in broilers - Freitas, Alfredo R. de; Pieniz, Luiz C.; Michelan Filho, Tércio; Rosso, Luiz A. de (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out in order to study the reaction of body weight and digestive tract to age in Pilch broilers. It was run in Concórdia, SC, from April to June of 1982. Rations ad libitum ware utilized as follows: starting from 1 to 28 days old (2970 kcal/kg ME and 22.8 percent crude protein) and finishing ration-from to 70 days of age, (3050 kcal/kg and 19.8 percent crude protein). Gompertz' model was adjusted for body weight, and polynomial regressions were adjusted for digestive tract. Irrespectively of sex, the adjusted coefficients of determination (R2) for Gompertz' equation were higher than 98%, and prediction errors (PE) were lower than 10%. The coefficients of the estimates of polynomial regressions relating the digestive tract constituents to age were highly significant (P<0.01), and R2 values were higher than 70%, showing desirable traits in respect of adjustment. At seventy days of age, the maturity rate was 64% for males and 69% for females. The highest weight gains were 65.1 g at 43 days of age (males) and 49.2 g at 45 days of age (females).